Asuhan Keperawatan Masalah Sesak Pada Anak Usia Toddler dengan Infeksi Saluran Pernapasan Akut (ISPA) di Rumah Sakit Syekh Yusuf Kabupaten Gowa - Yuli Setianingrum; Kasmawati K; Rudi Salam (Prodi Keperawatan Universitas Syekh Yusuf Al Makassari Gowa, 2025)
Acute respiratory tract infection (ARI) is a very common disease found with mild to severe manifestations and is the cause of death highest in toddlers. In ARI patients, response activation occurs immune system then the mediator's activity decreases so that secretion production increases and result in ineffective airway clearance. The aim of this author is Describe nursing care for patients with nursing problems ineffectiveness of airway clearance in cases of ARI with special therapeutic interventions chest The method used is a case study with nursing care in two cases patients and carry out assessments, nursing diagnoses, action plans nursing, nursing actions, and evaluation. Data collection was carried out by using interview methods, and physical examination, after that nebulizer and chest physiotherapy were carried out. Results from applying chest physiotherapy for 3 consecutive days to patients It was found that airway clearance was ineffective. The conclusion of this case study is that after implementing chest physiotherapy on ARI patients with nursing ineffectiveness problems. That's expected Chest physiotherapy can be applied in nursing care for clients with problems Nursing care for ineffective airway clearance can be carried out by the family clients independently at home.